Downregulation of MicroRNA-193b-3p Promotes Autophagy and Cell Survival by Targeting TSC1/mTOR Signaling in NSC-34 Cells - Li, ChunYu; Chen, YongPing; Chen, XuePing; Wei, QianQian; Cao, Bei; Shang, HuiFang (Frontiers in Molecular Neuroscience, 2017)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the death of upper and lower motor neurons. MicroRNAs (miRNAs) are reported to be closely related to the development of ALS. However, the precise functions of miRNAs in the pathogenesis of ALS remain largely unknown. In previous studies, we determined that miRNA-193b-3p was significantly downregulated in patients with sporadic ALS (sALS). Here, we observed that miRNA-193b-3p was downregulated in the SOD1G93A mouse model of ALS and promoted cell death in NSC-34 cells. We further found that miR-193b-3p directly targeted tuberous sclerosis 1 (TSC1) to regulate mechanistic target of rapamycin complex 1 (mTORC1) activity. Downregulation of miR-193b-3p led to TSC1 increase accompanied with mTORC1 inactivation, and vice versa. Moreover, downregulation of miR-193b-3p promoted protective autophagy and cell survival in NSC-34 cells. In contrast, upregulation of miR-193b-3p activated mTORC1 signaling, leading to inhibition of autophagy and promotion of cell death. Taken together, our study suggests that downregulation of miR-193b-3p is required for cell survival by targeting TSC1/mTOR signaling in NSC-34 cells and provides a novel target for improving the clinical therapy of ALS.